STRATEGI GURU DALAM MENINGKATKAN KARAKTER 6S MELALUI POSTER DAN SLOGAN - Putra Kaslin Hutabarat Putra (Biormatika : Jurnal ilmiah fakultas keguruan dan ilmu pendidikan, 2021)
The purpose of this study was to describe the strategies used in improving 6S in SD / MI. This journal uses a descriptive approach, observation data collection techniques, and interviews. Meanwhile, the data analysis technique uses an interactive model. Then test the validity of the data using data triangulation. And the strategy used is to use posters, slogans and posters that are displayed in class and outside the classroom. The results of this study are proven by showing a friendly and fully open attitude with good character, the language style starts from the greeting sentence. which is an example applied by the teacher when going into the room to shake hands and pray together. So it can be concluded that the existence of posters and slogans can increase the attitude and attitude of grade III students